Response to corticosteroids and alternative therapies in sarcoidosis-related hypercalcemia: A guideline-lacking retrospective analysis - Robinson, Drew; Crumpler, Denver; Zhai, Guihua; Barney, Joseph (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis is a systemic inflammatory disease of unknown etiology that can affect multiple organs including a known complication of hypercalcemia. Many therapies, both steroidal and nonsteroidal, have been employed. However, the optimal therapy for hypercalcemia in sarcoidosis is unknown, with most data from case reports and small case series. More information is needed to determine which nonsteroidal agents control hypercalcemia in sarcoidosis patients, particularly for populations in whom steroids should be avoided. We sought to answer the question, which pharmacological agents control hypercalcemia in patients diagnosed with sarcoidosis?Methods: We performed a retrospective chart review on all adult patients at our hospital a diagnosis of Sarcoidosis and Hypercalcemia and a recorded calcium level of greater than 10.4 mg/dL. We then determined which agents were able to control their calcium to a level of 10.4 mg/dL or less for at least 6 months and 12 months.Results: The most common efficacious treatments were prednisone, methotrexate, hydroxychloroquine, and prednisone + methotrexate. A positive linear relationship was found between ACE and highest calcium levels. No significant relationship between organ involvement or race and highest calcium levels were noted.Conclusions: There is currently little data or guidelines to best guide the treatment of hypercalcemia in sarcoidosis. This study represents the first with the primary aim to compare treatment options for hypercalcemia in sarcoidosis across a large cohort. Several non-steroidal options were identified that controlled hypercalcemia as a single agent. In addition, this study further investigated potential biomarkers for abnormal calcium metabolism as well as the relationship between calcium levels and organ involvement/race. Further work is needed to determine the most effective steroid sparing therapy to control hypercalcemia in sarcoidosis.